2021
DOI: 10.1186/s12957-021-02384-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a six-gene prognostic model for cervical cancer based on WGCNA combined with LASSO and Cox-PH analysis

Abstract: Aim This study aimed to establish a risk model of hub genes to evaluate the prognosis of patients with cervical cancer. Methods Based on TCGA and GTEx databases, the differentially expressed genes (DEGs) were screened and then analyzed using GO and KEGG analyses. The weighted gene co-expression network (WGCNA) was then used to perform modular analysis of DEGs. Univariate Cox regression analysis combined with LASSO and Cox-pH was used to select the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…PPIA (Cyclophilin A) is a member of the immunophilin family and acts as an immune inflammatory mediator that secretes oxidative stress-induced, which promotes the formation of foam cells by increasing the levels of ROS and pro-inflammatory cytokines. Furthermore, PPIA is involved in biological processes such as intracellular signaling, transcription, and apoptosis, therefore playing critical roles in microorganismal infections, inflammatory diseases, and tumor proliferation [32][33][34]. An increase in PPIA levels may lead to macrophage apoptosis through activation of mitochondrial death signaling pathways and caspase 3 cascade [35].…”
Section: Discussionmentioning
confidence: 99%
“…PPIA (Cyclophilin A) is a member of the immunophilin family and acts as an immune inflammatory mediator that secretes oxidative stress-induced, which promotes the formation of foam cells by increasing the levels of ROS and pro-inflammatory cytokines. Furthermore, PPIA is involved in biological processes such as intracellular signaling, transcription, and apoptosis, therefore playing critical roles in microorganismal infections, inflammatory diseases, and tumor proliferation [32][33][34]. An increase in PPIA levels may lead to macrophage apoptosis through activation of mitochondrial death signaling pathways and caspase 3 cascade [35].…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to improve patient prognosis and quality of life deserve further study. It is reported that abnormal expression of important genes and alterations of signaling pathways are associated with cancer pathogenesis [ 23 , 24 ]. For instance, Qin F et al revealed a novel angiogenesis subtype classification in squamous cell carcinoma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that abnormal expression of important genes and alterations of signaling pathways are associated with cancer pathogenesis [ 23 , 24 ]. For instance, Qin F et al revealed a novel angiogenesis subtype classification in squamous cell carcinoma [ 23 ]. Li S et al screened six prognostic hub genes by weighted gene co-expression network analysis (WGCNA) combined with LASSO Cox-PH analysis, which provided a new strategy for targeted therapy of cervical cancer [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The predictive power of multivariate Cox regression analysis is better than that of univariate Cox regression analysis because univariate Cox analysis is easily affected by the bias of univariate significant variables. The predictive power of multivariate regression to establish a prognostic model is better than that of univariate Cox regression [ 38 ]. Combining the use of eight bioinformatics tools to establish the BLCA prognostic model increases model accuracy, reduces model-independent variables, and improves predictive sensitivity and depth.…”
Section: Discussionmentioning
confidence: 99%